Efektivitas Model Pembelajaran SQ3R dengan Media Flipbook terhadap Kemampuan Membaca Permulaan pada Siswa Kelas 1 Sekolah Dasar - Tryfosa Pascha Agellia; Rissa Prima Kurniawati; Elly’s Mersina Mursidik (Nusantara: Jurnal Pendidikan Indonesia, 2026)
Purpose – This study aimed to examine the effectiveness of the SQ3R learning model assisted by Flipbook media in improving beginning reading skills among first-grade elementary school students.Methods – This study employed a quantitative approach using a pre-experimental One-Group Pretest–Posttest design involving one experimental class. Beginning reading skills were measured using a structured reading fluency test covering letter recognition, syllable reading, word reading, reading speed, intonation, expression, and reading comprehension. Data were analyzed using a paired-samples t-test. Findings – Descriptively, the mean posttest score was higher than the mean pretest score, indicating an improvement in students' beginning reading skills after the implementation of the SQ3R learning model assisted by Flipbook media. However, the paired-samples t-test showed that the difference was not statistically significant (t (48) = -0.612, p = .543). Therefore, the study did not provide sufficient statistical evidence to conclude that the intervention significantly improved beginning reading skills.Research Implications – Although students' reading performance improved descriptively, the statistical findings indicate that the effectiveness of the intervention could not be confirmed. The absence of a control group and the use of a single experimental class limit the generalizability of the findings. Future studies are recommended to involve larger samples and a control group to obtain stronger empirical evidence.